"CorAMARal": O engajamento musical transformativo e suas ressonâncias para uma aprendizagem autônoma e transformação social - Alves, Vicente de Paulo Barroso (2021)
The present research aims to investigate how the teaching of arts in elementary school impacts on the participants’ transformative engagement. The research analyzed CorAMARal, a choir group formed by students from the 5th to the 9th grade of elementary classes of a municipal school. CorAMARal is an activity that occurs on a after class period with spontaneous participation of the members, as part of extracurricular training. During the study it was noticeable that the activity was efficient to foster students’ autonomous search for new artistic knowledge - especially musical ones – and to contribute to social transformation and to citizenship development. The research focused on the processes inherent to CorAMARal that, each year, culminate on presentations of the group authorial artistic show invention. Operating since 2017, the choir has gone through three different formations, with different characteristics, because it shapes itself according to the contributions brought by the participants. Professor and researcher Susan O’Neill’s Transformative Music Engagement (2012) theory served as reference to this study. Methodological guidance was draw from Cartography as understood by Gilles Deleuze and Félix Guatari (1997) and Kastrup (2015), respecting the concept of rhizome. Among the results of the present study, worth mentioning CorAMARal’s potential to promote musical engagement. Nevertheless, it is important emphasize that, during each process, there is particular ways for appropriating the musical and extramusical knowledge. In this sense, it is essential to consider that everyone – participant students, educator/researcher, school, schedule organization and presentations – may have an impact on the engagement. It is also notorious that group participant’s engagement reverberated in their lives and social nets (that is, family, friends and community in general), once they start acting themselves as engines for social transformation and citizenship